Capitalism, alone the future of the system that rules the world - Milanović, Branko (The Belknap Press of Harvard University Press, 2019)
"For the first time in history, the globe is dominated by one economic system. Capitalism prevails because it delivers prosperity and meets desires for autonomy. But it also is unstable and morally defective. Surveying the varieties and futures of capitalism, Branko Milanovic offers creative solutions to improve a system that isn't going anywhere"--